Effects of Foliar Spraying of Dicarboxylicdimethylammonium Chloride on Cadmium and Arsenic Accumulation in Rice Grains - Lin Fu; Jiawei Deng; Dayliana Ruiz Lao; Changbo Zhang; Weijie Xue; Yun Deng; Xin Luo (Toxics, 2024)
A field experiment with double cropping rice was carried out to study the foliar application effects of dicarboxylicdimethylammonium chloride (DDAC) on cadmium (Cd) and arsenic (As) accumulation in rice grains. The results showed that the spraying of DDAC could significantly reduce the accumulation of Cd and As in rice grains. The highest reductions in Cd and As content were observed when 1.5 mmol L−1 DDAC was sprayed, with 49.1% and 27.4% reductions in Cd and As content in early rice grains and 56.5% and 28.1% reductions in Cd and As content in late rice grains, respectively. In addition, the content of calcium (Ca) in rice grains increased significantly after DDAC foliar application, which was also conducive to the synthesis of amino acids such as glutamate (Glu), glycine (Gly) and cysteine (Cys) in rice grains. The results indicated that the foliar spraying of DDAC can inhibit the absorption, transport, accumulation and toxicity of Cd and As in rice grains by increasing amino acid synthesis and regulating the absorption and transport of essential elements.